INTERNALISASI HADIS ANTIKEKERASAN DALAM DUNIA VIRTUAL UNTUK MENANGGULANGI CYBERBULLYING: Studi Grounded Theory - Khodijah Firdaus; Sholahuddin Al Ayubi (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
This study aims to explore how people interpret and internalize hadith messages when facing cases of digital bullying, using Kathy Charmaz's Constructivist Grounded Theory approach. This approach allows the exploration of personal experiences and in-depth reflections from individuals who have been victims, perpetrators, and witnesses of cyberbullying. Data were obtained through in-depth interviews and analyzed gradually to form theoretical concepts that represent the construction of meaning from the participants' perspectives. The findings of this study reveal that hadith values such as the importance of guarding speech, the prohibition of harming others, and the invitation to do good contribute to the birth of new awareness in responding to the dynamics of cyberspace, including the development of digital empathy, the ability to restrain oneself, and the application of media ethics. Therefore, when interpreted contextually and embedded in the collective consciousness, hadith has the potential to become a spiritual-transformational force in creating a more ethical, civilized and humane digital space.